Supporting 21st century English teaching and learning through Google Classroom at university level - Linda Septiyana; Widiyaningsih Widiyaningsih (Universitas Lampung, 2020)
English teaching and learning in the 21stcentury is demanded to be technology-based to balance demands in the digital age. In this digital age there are various ways of learning besides being in the classroom, one of which is through the use of e-learning, namely Google Classroom. The purpose of this study is 1) to reveal the design of English teaching and learning using Google Classroom for English Education Department Students of IAIN Metro, 2) to identify students’ responses toward the use of Google Classroom in English teaching and learning. This study is qualitative in the form of field research. English teaching and learning was carried out by implementing Google Classroom at the third semester students of English Education Department IAIN Metro. This research showed that Google Classroom can facilitate both students and lecturers in conducting English teaching and learning process more comprehensively. This is because both students and lecturers can provide learning materials, give questions, collect assignments, distribute assignments, and assess assignments anytime and anywhere. http://dx.doi.org/10.23960/aksara/v21i1.pp102-114